Effect of the Wnt/β-catenin pathway inhibitors on cell proliferation and migration of HEC-1A endometrial adenocarcinoma: experimental cell culture model - Çirçirci, Yaşam; Tiftik, R. Nalan; Ün, İsmail (The European Research Journal, 2021)
Objectives: The most diagnosed tumor among infiltrating tumors of the female genital tract is endometrial carcinoma. The Wnt/β-catenin signaling pathway has an important role in organogenesis, self-renewal of tissues, and adult stem cell maintenance. However aberrant activation of it causes many types of tumors and also related to the prognosis of patients. Therefore, we aimed to investigate whether Wnt/β-catenin pathway inhibitors have any effect on the proliferation and migration of tumor cells. Methods: As cancer cell line, HEC-1A endometrial adenocarcinoma was used. The Wnt/β-catenin pathway inhibitors effects on proliferation and migration were demonstrated by real-time cell analysis device and wound healing model respectively. Results: Wnt/β-catenin pathway inhibitors FH535 (25 μM at 36th hour, p < 0.05; 50μM at 48th hour p < 0.001) and niclosamide inhibited cell proliferation (10, 25 and 50μM at 60th hours; p < 0.01, p < 0.05 and p < 0.001, respectively) whereas ICRT14 and IWP-2 did not. However only niclosamide which is also an antihelmintic drug inhibited migration of the cells in all concentrations tested (10, 25 and 50μM, p < 0.05). Conclusions: The present study shows that the Wnt/β-catenin pathway has an substantial role in both proliferation and migration of endometrial adenocarcinoma. We suggest that the antihelmintic drug niclosamide could be further investigated for its potential therapeutic effect in endometrial adenocarcinoma.